A sustainable approach for planning of urban pedestrian routes and footpaths in a pandemic scenario - Cirianni, Francis M. M.; Comi, Antonio; Luongo, Angelo S. (TeMA - Journal of Land Use, Mobility and Environment, 2022)
The coronavirus disease (COVID-19) pandemic has forced national and local governments to re-consider the relationship between mobility, urban space and health in order to ensure physical distancing while meeting the travel needs of inhabitants. In the first stage, corresponding to the expansion of infection, mobility was limited to essential workers and freight. In the second stage, with the easing of restrictions, limitations still remained for public transport. Limitations associated with perceived risk of infection significantly influenced travel behaviors, pushing a modal repositioning in demand to active mobility (walking, cycling, and use of micro-mobility). On the other hand, the World Health Organization (WHO) guidelines on mobility during the COVID outbreak are mostly directed at dedicating more urban space to cyclists and pedestrians, especially in densely populated urban areas, thus avoiding crowding on public transport and the use of private cars. In the same direction, the National Association of City Transportation Officials (NACTO, 2020) went during periods of stabilization and long-term recovery. It suggests policies and measures for the cities mobility to help people maintain physical distance while moving around the city. In the given conditions, walking becomes predominant for a sustainable mobility scenario, and structural measures (widening of the pathway) or regulatory measures (regulation of pedestrian flows) can be adopted withing the given strategy. Current pedestrian infrastructural offer is severely limited in functional terms by the urban planning and development, therefore measures oriented to enhance non-motorized mobility require the development and planning of new public spaces and infrastructures for pedestrian mobility within the urban layout. Policy makers and town planners need to rethink urban spaces and mobility in the pedestrian perspective. A methodology for classification of pathways, by capacity and level of service, is presented in the paper, on which to base strategies, policies and specific measures to verify pedestrian mobility demand.